(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article examines environmental issues related to plastic waste in the context of various regions and countries of the world as one of the negative factors in the modern world. It also examines environmental issues of plastic waste that have a negative impact on public health. A comparative analysis of the causes of environmental problems of plastic waste at the present stage is given.